Teacher violence, school satisfaction and subjective well-being in children and adolescents in residential care: The moderation effect of staff support - Ortúzar, Harry (2021)
This study involved 608 children and adolescents between 7 and 18years of age (Mage=12.9, SDage=2.70) from 47 residential care centres in Peru (RCC). The objective of the study was to observe the mediating effect of school satisfaction on the relationship between violence by teach-ers at school and the subjective well- being of children and adolescents, considering how the low or high support from residential care staff can condition this mediating effect as well. The descriptive results show a very high prevalence of violence inflicted by teachers at school for both children and adolescents in residential care in Peru. Regarding the results obtained from the moderated mediation model re-sults, the school satisfaction domain is observed to have a mediating effect on the relationship between teacher violence and subjective well- being in children and ado-lescents. In addition, a moderated mediation effect condi-tioned by support from residential care staff is seen only in the case of children.